State and Crafts in the Qing Dynasty (1644-1911) - Moll-Murata, Christine (Social Histories of Work in Asia, 2018)
This book, full of quantitative evidence and limited-circulation archives, details manufacturing and the beginnings of industrialisation in China from 1644 to 1911. It thoroughly examines the interior organisation of public craft production and the complementary activities of the private sector. It offers detailed knowledge of shipbuilding and printing. Moreover, it contributes to the research of labour history and the rise of capitalism in China through its examination of living conditions, working conditions, and wages.